Effect of High-Fat Diet Variations on Cholesterol Levels and Hepatic Histopathology in Mouse Models of Type 2 Diabetes Mellitus - Hanna, Dhea Nisa; Qomariyah, Nur (LenteraBio : Berkala Ilmiah Biologi, 2025)
Excessive consumption of fatty foods causes lipid accumulation, leading to hypercholesterolemia and type 2 diabetes mellitus. This study aims to determine the effect of a high-fat diet with various fat types together with alloxan induction on cholesterol levels and hepatic histopathology. This study used a completely randomized design (CRD); twenty male mice were divided into five treatment groups, namely KK (standard feed), KP (placebo), P1 (vegetable oil), P2 (beef tallow), and P3 (goat tallow). The feed, fat, and duck egg yolk ratio was 80%:15%:5% given ad libitum at a dose of 5 gram/day for eight weeks, followed by alloxan injection to induce diabetes mellitus in mice. Liver histopathology were prepared using paraffin method and Hematoxylin-eosin (HE) staining. Hepatocytes were assessed based on inflammatory damage, swelling, and steatosis. Total cholesterol levels were analyzed by ANOVA, followed by Duncan’s test. Kruskal-Wallis test followed by Mann-Whitney was used to analyzes liver histopapathology. Total cholesterol levels of P2 had drastic increased every week. Hepatic histopathology showed significant differences between groups. It can be concluded that a high-fat diet using beef tallow had the highest effect to type 2 diabetes mellitus in regards to total cholesterol levels at 132±4.24 mg/dL and hepatic histopathology, resulting in steatosis.